Investigation of Vitamin D Levels in Iraqi Patients with Type 2 Diabetes Mellitus: A case- control study - Esraa S. Al-Fatlawey; Esraa S. Al-Fatlawey (Zien Journals, 2023)
Vitamin D deficiency is common in most regions of the worldwide. Its deficiency or insufficiency is implicated in cardiac disease, infectious diseases, bone disorders, autoimmune and metabolic diseases, such as type 2 diabetes mellitus (T2DM). This study aims to investigate the association between vitamin D levels and development of T2DM in Iraqi population
Keywords: T2DM; Vitamin D; Insulin Resistance